Standards and requirements for the development of battery energy storage system (BESS) based virtual power plant (VPP) - Abdullah W.S.W.; Osman M.; Ab Kadir M.Z.A.; Verayiah R. (Alpha Publishers, 2023)
The power system is facing new challenges with anticipated higher penetration of Renewable Energy (RE) resources. Among others, Solar Power, other RE resources such as mini hydro, biomass, biogas and Battery Energy Storage System (BESS) is gaining popularity in terms of deployment. Virtual Power Plant (VPP) is relatively new concept of combining RE resources including BESS to serve as one power plant and able to be controlled by an aggregator system. VPP enhanced by BESS is capable in serving few utility and customers challenges. It has been identified that BESS can serve few applications such as to cut peak demand, energy arbitrage, spinning reserve, frequency regulation, and reducing the intermittency of renewable resources. It is foreseen that the role of BESS can be crucial with a higher increase of RE penetration of power system. This paper will cover technical and non-technical requirements for BESS and VPP development. 2020 Alpha Publishers.